Optimalisasi Video Pendek Media Sosial dalam Penggunaan Aplikasi Capcut sebagai Media Pembelajaran - Syarifudin, Achmad (Universitas Sunan Drajat Lamongan, Indonesia, 2024)
This community service activity focuses on training on the use of short social media videos as a learning medium. The aim of this service is to develop the skills of lecturers at the Faculty of Social and Cultural Sciences, Trunojoyo University, Madura, to be able to make videos as a good learning medium. The method for implementing this service activity is in the form of training regarding the use of short social media videos and practice in creating video content through the CapCut application. The results of this service show an increase in participants' understanding and skills in creating learning video content and through this activity it is hoped that educators, namely lecturers, can be more effective in providing learning material by utilizing short video content as learning media.